An econometric model of beef production for optimization purposes - Sirén, Jouko (Agricultural and Food Science, 1978)
The aim of this study was to create a model depicting the growth process of a beef animal to provide means for economic optimization of the slaughter weight and of the length of the rearing period. Using data from Finnish beef rearing experiments, a model with two functions, one for weight gain and the other for feed intake, was estimated. In weight gain functions total energy and digestible crude protein were the main explanatory variables. Intake capacity of the animal was estimated as time needed to consume the dry matter quantity of a given feed input using also protein, crude fibre content and energy content of feed as explanatory variables. The model was estimated separately for Ayrshire bulls and for Friesian-Ayrshire and Charolais-Ayrshire cross-breeds. Functions of Cobb-Douglas or transcendental forms gave the best fits and turned out to be logical. Information given by the regression coefficient estimates was analyzed in detail as background for applications of the model. When dealing with the optimization problem the dynamics of production was discussed and a maximum daily profit was selected as the optimization criterion. An example was then presented to illustrate the profit maximization. Since they were of essential importance in the production economy, the feed composition and its productivity were analyzed and an example was derived to minimize the price of feed mix with maximum productivity.